A Ribosomopathy Reveals Decoding Defective Ribosomes Driving Human Dysmorphism - Paolini, Nahuel A. (Am J Hum Genet, 2017)
Ribosomal protein (RP) gene mutations, mostly associated with inherited or acquired bone marrow failure, are believed to drive disease by slowing the rate of protein synthesis. Here de novo missense mutations in the RPS23 gene, which codes for uS12, are reported in two unrelated individuals with microcephaly, hearing loss, and overlapping dysmorphic features. One individual additionally presents with intellectual disability and autism spectrum disorder. The amino acid substitutions lie in two highly conserved loop regions of uS12 with known roles in maintaining the accuracy of mRNA codon translation. Primary cells revealed one substitution severely impaired OGFOD1-dependent hydroxylation of a neighboring proline residue resulting in 40S ribosomal subunits that were blocked from polysome formation. The other disrupted a predicted pi-pi stacking interaction between two phenylalanine residues leading to a destabilized uS12 that was poorly tolerated in 40S subunit biogenesis. Despite no evidence of a reduction in the rate of mRNA translation, these uS12 variants impaired the accuracy of mRNA translation and rendered cells highly sensitive to oxidative stress. These discoveries describe a ribosomopathy linked to uS12 and reveal mechanistic distinctions between RP gene mutations driving hematopoietic disease and those resulting in developmental disorders.